The role and status of women in Sikhism - Gilla, Mahindara Kaura (Delhi : National Book Shop, 1995)
Biographical sketches of ten Sikh guru's consorts with special emphasis on Mata Sundari, 1667-1747
Includes bibliographical references (p. 105-106)
Keywords: Mata Sundari, -- 1667-1747; Sikh women -- India -- Biography; Sikh gurus